Etiologi, Distribusi Lokasi, dan Terapi Ulser Traumatik pada Pasien di Rumah Sakit Gigi dan Mulut Universitas Padjadjaran - Erna Herawati; Nanan Nur'aeny (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Oral mucosal ulceration can be caused by local or systemic factors. One of the local factors often expressed by patients is the result of being bitten. Research data on oral mucosal ulceration has not been widely published, especially in Indonesia, so the purpose of this study was to provide information on the etiology, site distribution and therapy of traumatic ulcers in patients at the Dental Hospital, Universitas Padjadjaran (RSGM Unpad). Methods: A descriptive study, with data obtained secondary from the medical records of patients at the RSGM. Data presentation is done by tabulation and percentage. Results: There were 44 patients consisting of 15 males (34.05%) and 29 females (65.95%), with an age range of 17 – 55 years. Trauma which is the most common cause of ulcers is due to accidentally biting, the most common site is the buccal mucosa, and the most widely used drug is a combination of vitamins and anti-inflammatory which was given to 10 patients with traumatic ulcers (22.7%). Conclusion: The most common cause of oral ulcers is trauma, and the most common trauma in adults is the result of accidentally biting.